Diversity of Bats in Fragmented Forest and Oil Palm Plantation - Nor Fatin Najihah, Mohamad Zulkifli (Universiti Malaysia Sarawak (UNIMAS), 2015)
Research on the diversity of bats in fragmented forest and oil palm plantation had been done in Segarmas and Saremas 2 Estate, Wilmar Plantation Estate PPB Oil Palm Berhad, Miri, Sarawak from August 2014 until April 2015. The study was carried out in order to investigate the difference in diversity of bats at fragmented forest, oil palm plantation and forest edge. Eight transects that consisted of fragmented forest and oil palm plantation was selected. 21 mist nets had been deployed for every sampling and two to four harp traps had been set up along the transects. Total sampling day was 25 days. A total of 337 individuals with 14 species from six families had been captured. 6 I individuals were captured in the fragmented forest that consists of 10 species and from six families. In oil palm plantation, a total of 201 individuals were captured that consist of nine species and from four families. At edge, a total number of 75 individuals were captured· that consist of eight species and from four families. The most abundant species from all sites was Cynopterus brachyotis with a total number of 242 individuals were captured for this species (71.8%), followed by Hipposideros cervinus with 51 individuals (15.1 %). Fragmented forest had the most diverse bat species (H'=l753 ), followed by oil palm plantation (H'=0.800), while the edge is the less diverse (H'= 0.543), This study showed that there is a significant difference between oil palm plantation and fragmented forest and between fragmented forest and edge. But, it is not significant between oil palm plantation and edge.